MEDIA MASS A DAN MULTIKULTURALISME (Studi Kasus Koran Kaltim Post dan Radio Darussalam Samarinda) - la mansi (Al-Qalam, 2007)
This study was conducted in Samarinda, East Kalimantan. Focus studyis Kaltim Post Newspaper and Radio Darussalam Samarinda. This researchaims to describe the role mass media in socializingmulticulturalism idea. This use qualitative method, where data wascollected using interview and article searching, and then, analyzed bycritical discourse analysis.This study indicates that there are two perspectives used by Kaltim Postin reporting on culture and religious problem. The perspectives areartificial perspective and analytical perspective. While, the RadioDarussalam, its program only broadcast Islam mission from variousstream and organization that exist in Islam tradition